Evaluating the Efficacy of Ayurvedic Herbs in Menstrual Disorder Treatment: A Comprehensive Review (AYUSHDHARA, 2025)
The use of Ayurveda is gaining more importance and acceptance in overall clinical practice. Women's health is an important concern of the public health system today. Irregular menstruation is a common problem among all age groups of women. In traditional medicine, especially in Ayurveda, a large number of women were treated for this incomplete physical problem. Ayurveda is an ancient Indian science of life. It is based on lifestyle, diet, yoga, meditation, and the use of medicinal plants to control severe diseases. In the modern scientific era, many researchers are engaged in rare traditional medicines. The world is seeking new physiotherapies and is very interested in ancient traditional medicine. Our aim is to document a review of medicinal herbs used to treat menstrual disorders in Ayurveda and to demonstrate scientifically the pharmacological properties in the treatment of Ayurvedic medicinal herbs for menstrual disorders in the future. It is important to carry out research into traditional knowledge in combination with other systems of medicine such as modern medicine. Hence, this review paper is an attempt to document the conventional knowledge and research information about Ayurvedic herbs used to treat menstrual disorders and to reveal possible research gaps. This review paper included clinical information about traditional uses, pharmacological validation, efficacy, and safety aspects of the use of medicinal herbs in the treatment of menstrual disorders. The preliminary findings highlighted the efficacy of Ayurvedic herbs that can be used clinically by the practitioner. Further clinical research and clinical studies are recommended to validate the combined therapeutic effects in the treatment of menstrual disorders.